The Role of Peers in Students' Academic Achievement: A Qualitative Study from an Educational Psychology Perspective - Fadilla Neva Ariyana; Siti Nurlaila; Jauharotul Ulum; Surawan Surawan (unprimdn.ac.id, 2026)
This study aims to analyze the role of peers on students' academic achievement from an educational psychology perspective using a qualitative, descriptive phenomenological approach. The study was conducted at the State Islamic University of Palangka Raya with active student participants selected purposively based on high, medium, and low academic achievement categories. The selection of participants was carried out to obtain a variety of experiences regarding the influence of peer interactions on the learning process in the university environment. Data were collected through an initial questionnaire and in-depth interviews to explore students' experiences, perceptions, and the dynamics of social relationships within academic friendship groups. Data validity was carried out through source triangulation, technical triangulation, and member checking. Data analysis used the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results showed that peers have a significant influence on students' academic achievement. Positive influences are seen through academic support, increased learning motivation, information exchange, and learning behavior modeling that helps students understand lecture material and increase learning engagement. Interactions in small groups or circle study groups also encourage self-confidence and academic cooperation. However, this study found negative influences in the form of learning distractions, procrastination, imbalanced contributions within groups, and social pressure that can reduce students' focus on learning. These findings indicate that the role of peers is dynamic and contextual, necessitating appropriate management of social interactions through academic mentoring and peer mentoring programs to optimize the positive impact on student academic achievement.